The impact of Alpinia galanga rhizome fortification on the nutritional profile, antioxidant capacity and sensory characteristics of White Lacy Pancake (appam) - Debopriya Mandal; Sarita Roy; Runu Chakraborty (Discover Food)
Abstract Introduction Appam (White Lacy Pancake) is a traditional cereal-based fermented dish made from white rice and coconut. However, as the main ingredient of appam is dehulled and milled white rice, many essential nutrients are lost during processing. This study investigates the use of galangal rhizome (Alpinia galanga) to enhance appam’s sensory attributes and nutritional profile. Methods In the preliminary experiment, galangal rhizome was dried at various microwave powers, such as 360 W, 720 W, and 900 W, to get maximum TPC, TFC, and FRAP values. Appam samples were prepared by using three process parameters: cooking times (1–6 min), fermentation times (5–18 h), and various amounts of Galangal rhizome (1–6%). Five polyphenols were detected by HPLC analysis of appam samples: myricetin, vanillic acid, gallic acid, quercetin, and catechin. Proximate composition, mineral composition (using EDAX), and sensory experiments were also carried out to identify the role of galangal rhizome substitution in appam. Results It was found that galangal rhizome dried at a microwave power of 900 W showed the maximum TPC (Total Phenolic content), TFC (Total Flavonoid content), and FRAP (Ferric Reducing Antioxidant Power) values. Optimum processing parameters (3.50 min, 11.50 hours, and 3.50%) were obtained by considering the maximum TPC of the Appam samples through the Box-Behnken model. The fortification of appam samples enhanced the amounts of total polyphenol content, total flavonoid content, 2, 2’-Azinobis (3-ethylbenzothiazoline-6 sulfonic acid) radical scavenging property, and ferric reducing antioxidant activity by 22.30%, 28.25%, 66%, and 87%, respectively. The fortification of appam samples enhanced the amounts of myricetin, vanillic acid, gallic acid, quercetin, and catechin by 68%, 89.77%, 32.43%, 45.21%, and 24.39%, respectively. The pharmacological activities of these polyphenols include anti-inflammatory, antiobesity, anticancer, antidiabetic, and osteoporosis. The fortified appam samples increased the protein, ash, fibre, and carbohydrate contents. Conclusion The results of these trials indicated that adding galangal rhizome to appam significantly improved its nutritional content, antioxidant activity, and sensory qualities. Antioxidants can prevent food deterioration by suppressing oxidation. Fortified appams containing higher amounts of antioxidants also do the same. As a result, consumers might be able to use the product for longer.